1975
DOI: 10.1073/pnas.72.4.1523
|View full text |Cite
|
Sign up to set email alerts
|

Two classes of translational control RNA: their role in the regulation of protein synthesis.

Abstract: Two classes of translational control RNA (tcRNA) have been isolated from embryonic chick muscle. One of these classes, the tcRNA isolated from messenger ribonucleoprotein particles (mRNP-tcRNA), is effective in inhibiting the translation of mRNP-mRNA while having little if any effect on polysomal mRNA. The other class, polysome-tcRNA, has no effect on mRNP-mRNA while it stimulates the translation of polysomal mRNA. Translational control RNA (tcRNA) has been isolated from initiation factor preparations and has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1

Year Published

1976
1976
1989
1989

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(41 citation statements)
references
References 12 publications
3
37
1
Order By: Relevance
“…For regenerating liver and liver during microsomalenzyme induction, evidence has been obtained for a decrease in the activity of an inhibitor of aminoacyltRNA binding (Goodchild & Nicholls, 1976;Tominaga et al, 1975), as well as an increase in the activity of elongation factor 1 (Cappon & Nicholls, 1974a (Petryshyn & Nicholls, 1976). Further, the absence of a differential effect on initiation suggests that changes in an inhibitor affecting initiation, such as reported for tissues other than kidney, cannot account for the results reported here (Gross & Rabinowitz, 1972;Lodish & Desalu, 1973;Levin et al, 1975;Bester et al, 1975). The increased incorporation with the supernatant fraction of regenerating kidneys could not be attributed to the amount of mRNA in the preparation, since the increase was present when excess of poly(U) directed the peptide formation as well as when endogenous mRNA in the control-liver ribosome preparation directed incorporation.…”
Section: Discussioncontrasting
confidence: 52%
“…For regenerating liver and liver during microsomalenzyme induction, evidence has been obtained for a decrease in the activity of an inhibitor of aminoacyltRNA binding (Goodchild & Nicholls, 1976;Tominaga et al, 1975), as well as an increase in the activity of elongation factor 1 (Cappon & Nicholls, 1974a (Petryshyn & Nicholls, 1976). Further, the absence of a differential effect on initiation suggests that changes in an inhibitor affecting initiation, such as reported for tissues other than kidney, cannot account for the results reported here (Gross & Rabinowitz, 1972;Lodish & Desalu, 1973;Levin et al, 1975;Bester et al, 1975). The increased incorporation with the supernatant fraction of regenerating kidneys could not be attributed to the amount of mRNA in the preparation, since the increase was present when excess of poly(U) directed the peptide formation as well as when endogenous mRNA in the control-liver ribosome preparation directed incorporation.…”
Section: Discussioncontrasting
confidence: 52%
“…These mRNPs as well as mRNAs isolated thereof are inactive as templates in a cell-free translational system, owing to their bound translational inhibitor RNA, which can be dissociated in vitro from poly(A) mRNP or mRNA by poly(U)-Sepharose affinity chromatography in the presence of 10 mM EDTA (2). Similar translational inhibitor RNAs associated with mRNPs have also been detected in the embryonic chicken muscle (3,4), duck erythroblasts (5), rat connective tissue (6) as well as in Artemia salina embryos (7).…”
Section: Introductionmentioning
confidence: 82%
“…Despite the considerable variation in the template activity of the post-ribosomal mRNA preparations (normal rat livers: 189,000-695,000 cpm; iron-treated rat liver: 261,000-554,000 cpm), very little variation was observed in the ratio: incorporation of radioactivity into ferritin/incorporation of radioactivity into total protein (Table 2, last column) within the two types of post-ribosomal mRNA preparations (normal rat liver: 0.39-0.56; iron-treated rat liver: 0.11-0.13). Bester et al (43) have demonstrated the presence of translational control RNA (tcRNA) in the post-ribosomal supernatant from embryonic chick muscle and have shown that it inhibits the translation of the corresponding messenger ribonucleoprotein (mRNP). We have preliminary evidence that some of our post-ribosomal mRNA preparations contained variable amounts of translational control RNA which would explain the observed differences in their activities in the wheat germ system.…”
Section: Synthesis Of Ferritin By Liver Polyribosomal and Postribosommentioning
confidence: 99%